A population-based study of human immunodeficiency virus in south India reveals major differences from sentinel surveillance-based estimates - Kumar G Anil (BMC Medicine, 2006)
Abstract Background The human immunodeficiency virus (HIV) burden among adults in India is estimated officially by direct extrapolation of annual sentinel surveillance data from public-sector antenatal and sexually transmitted infection (STI) clinics and some high-risk groups. The validity of these extrapolations has not been systematically examined with a large sample population-based study. Methods We sampled 13838 people, 15–49 years old, from 66 rural and urban clusters using a stratified random method to represent adults in Guntur district in the south Indian state of Andhra Pradesh. We interviewed the sampled participants and obtained dried blood spots from them, and tested blood for HIV antibody, antigen and nucleic acid. We calculated the number of people with HIV in Guntur district based on these data, compared it with the estimate using the sentinel surveillance data and method, and analysed health services use data to understand the differences. Results In total, 12617 people (91.2% of the sampled group) gave a blood sample. Adjusted HIV prevalence was 1.72% (95% confidence interval 1.35–2.09%); men 1.74% (1.27–2.21%), women 1.70% (1.36–2.04%); rural 1.64% (1.10–2.18%), urban 1.89% (1.39–2.39%). HIV prevalence was 2.58% and 1.20% in people in the lower and upper halves of a standard of living index (SLI). Of women who had become pregnant during the past 2 years, 21.1% had used antenatal care in large public-sector hospitals participating in sentinel surveillance. There was an over-representation of the lowest SLI quartile (44.7%) in this group, and 3.61% HIV prevalence versus 1.08% in the remaining pregnant women. HIV prevalence was higher in that group even when women were matched for the same SLI half (lower half 4.39%, upper 2.63%) than in the latter (lower 1.06%, upper 1.05%), due to referral of HIV-positive/suspected women by private practitioners to public hospitals. The sentinel surveillance method (HIV prevalence: antenatal clinic 3%, STI clinic 22.8%, female sex workers 12.8%) led to an estimate of 112635 (4.38%) people with HIV, 15–49 years old, in Guntur district, which was 2.5 times the 45942 (1.79%) estimate based on our population-based study. Conclusion The official method in India leads to a gross overestimation of the HIV burden in this district due to addition of substantial extra HIV estimates from STI clinics, the common practice of referral of HIV-positive/suspected people to public hospitals, and a preferential use of public hospitals by people in lower socioeconomic strata. India may be overestimating its HIV burden with the currently used official estimation method.